Review of Scientific Publications on Money Laundering and Terrorist Financing in Major Hungarian Law Enforcement Journals over the Last 20 Years - Zsigmond, Csaba (Magyar Rendészet, 2025)
International and nation-state action against money laundering is of paramount importance, as this activity poses a major threat to the economic stability and public security of certain countries. The danger of money laundering is demonstrated by the fact that it is closely linked to organised crime, as organised crime groups seek to legalise their illicit proceeds through various methods of money laundering. The effective prevention, detection and proof of money laundering offences is therefore the basis for effective action against organised crime. The main objective of my literature research is to provide a comprehensive picture of the scientific results published in the last twenty years in the most prestigious law enforcement journals in Hungary. The research method was an online database search between 2004 and 2024, which contains articles from three Hungarian journals (Belügyi Szemle, Magyar Rendészet, and Rendészeti Szemle). As a result of the search and filtering, 13 relevant articles were found in the period under study. The published articles point out the harmful economic effects of money laundering, its history in Hungary, the changing Hungarian and European Union legal background, the various legal interpretations and dogmatic issues related to money laundering, the methods and trends of money laundering in practice, and some articles also discuss the crime of terrorist financing related to money laundering. It provides an excellent summary for both researchers and practitioners.